BIM Adoption in Managing Construction Risks amongst Malaysian Quantity Surveyors: Current Practice and Challenges - Ismail, Noor Akmal Adillah; Mohd Yousof, Mohd Nazareth; Adnan, Hamimah (International Journal of Sustainable Construction Engineering and Technology, 2021)
Building Information Modelling (BIM) is a technology that has received an impetus within the construction industry worldwide. It has also triggered a new approach of working in quantity surveying practice, replacing the conventional methods. In term of managing risks, BIM potentially detects conflicts during visualization process at the design phase, subsequently reduces possible costs risk at the pre-construction phase. However, there are few issues to be dealt with by the construction players in integrating BIM to manage risks in construction projects such as lack of experience and skilled individuals in an organization, lack of awareness amongst project stakeholders and the fragmented nature of the construction industry. These issues somewhat hinder the technology to be implemented effectively and contribute towards the slow development of BIM in the construction industry in Malaysia. Therefore, this study aims to explore the adoption of BIM technology in managing construction risks amongst Malaysian Quantity Surveyors by investigating the current practice and identifying its challenges. Data were collected using a questionnaire survey and the survey results were analyzed adopting descriptive analysis and Average Index by using SPSS. It was found that the current adoption of BIM technology in managing construction risks amongst Malaysian Quantity Surveyors is still at the low level of implementation, despite having high level of awareness on BIM usage in the construction industry. The findings confirmed that the challenges to adopt BIM are related to the upgrade of hardware to match with new technology, lack of clear and specific BIM guidelines, provision of BIM training for employees and high cost for new technology. The results should direct to the Malaysian Quantity Surveyors to be BIM-ready in improving the number of Quantity Surveyors of becoming experts in BIM technology to manage risks in construction projects.